Stem volume estimation from aerial photographs of an RPAS in Chanchamayo, Peru - Claros-Canales, Alvaro S. (2023)
The objective of this paper was to estimate the volume of a secondary forest located in the Chanchamayo valley by means of a volume equation as a function of crown diameter from the information captured by a remotely piloted aircraft system (RPAS). With the digital RGB camera of the RPAS, photographs of the secondary forest were taken with a 90% overlap between them. The flights were made at different heights, selecting the photographs taken at 100 m above ground level. With them, photomosaics were made, in which a sample of 50 trees whose crowns were visible was taken. These trees were measured in the field, obtained dbh, diameters at different heights, stem height and crown radius. The stem volume of each tree was calculated with the Smalian formula. With the data, it was determined that there are no significant differences between the crown diameters calculated in the field and those measured in the mosaic, with which an equation of the stem volume as a function of the crown diameter was elaborated, based on data from 40 sample trees, after analyzing seven volume equations models with eight weighting factors. The best equation was selected using the Furnival Index; thus, the best equation that estimates the stem volume of dominant trees of a young secondary forest in Chanchamayo is V = 0,18803451 + 0,00968219 dcopa2